Luci e ombre sulla valutazione dell’impatto sociale. La proposta del GECES - Marco Di Gregorio (Culture e Studi del Sociale)
The essay intends to explore some aspects of a methodology that looks at social enterprises’ activities through social impact measurement and assessment, in order to qualify and quan-tify the creating added-value, both in the community and to social enterprise itself. The fo-cus is on a document published in 2015 by the GECES Sub-group on Impact Measurement for the European Commission titled “Proposed Approaches to Social Impact Measurement in European Commission legislation and in practice relating to: EuSEFs and the EaSI”. The analysis of the proposed model aims to examine the actual possibilities of combining mar-ket competitiveness, product quality and solidarity. Looking at these issues raises attention to the risks related to the use of this model. From the point of view of subsidiarity, the es-tablishment of a single European market for social entrepreneurship financing, combined to application of a meritocratic principle, can pose a problem of equity, since in contradiction with the ideas and principles that govern the social action’s effectiveness.